2017
DOI: 10.1007/s10792-017-0745-6
|View full text |Cite
|
Sign up to set email alerts
|

Biometric evaluation of myopic eyes without posterior staphyloma: disproportionate ocular growth

Abstract: There is disproportionate elongation of the eyeball in myopic patients with very weak or no correlation between anterior biometry and AL. This discord is more in longer eyes. Such a scenario can be challenging to a refractive surgeon treating highly myopic eyes and needs further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Khokhar et al . 23 reported that the ACD and CCT did not lengthen based on the AL. Therefore, the longer the AL becomes, the longer the posterior vitreous body becomes, and the ARGOS defines the vitreous refractive index as 1.336.…”
Section: Discussionmentioning
confidence: 97%
“…Khokhar et al . 23 reported that the ACD and CCT did not lengthen based on the AL. Therefore, the longer the AL becomes, the longer the posterior vitreous body becomes, and the ARGOS defines the vitreous refractive index as 1.336.…”
Section: Discussionmentioning
confidence: 97%
“…Our results show that longer eyes had flatter corneas especially in subjects with high myopia which are consistent with the previously published studies. 17,33,34 Chang et al and Goss et al found that the anterior corneal surface was flatter in eyes with longer axial length. 17,35 Sang Hoon Park et al found that CC decreased as AL increased (r = -0.444, p <0.001), corneas were steeper in shorter eyes and flatter in longer eyes and they deduced that the reason might be an emmetropization effect to prevent myopic shift despite axial elongation.…”
Section: Discussionmentioning
confidence: 98%
“…We had noted a similar lack of correlation between anterior parameters in myopic patients in a previous study. [12] One may speculate these findings to have a simple mathematical explanation, that is, both AS and VCD contribute to AL. Hence, ratio of either of them to AL may have good relation to both.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of myopic eyes undergoing refractive surgery, we showed that there is a major discord between anterior biometry and the axial length (AL) of the eye ball. [12] We found the growth of the eye ball to be highly disproportionate, thus accounting for certain difficult scenarios surrounding refractive procedures. However, in that study we had noted an important limitation in our inability to evaluate VCD as a correlate of AL due to our sampling method.…”
mentioning
confidence: 99%
See 1 more Smart Citation